2021
DOI: 10.1161/jaha.120.016201
|View full text |Cite
|
Sign up to set email alerts
|

Objective Sleep Efficiency Predicts Cardiovascular Disease in a Community Population: The Sleep Heart Health Study

Abstract: Background There was little evidence about the role of objective sleep efficiency (SE) in the incidence of major cardiovascular disease (CVD) events. The purpose of this study was to investigate the correlation between objective SE and CVD based on polysomnography. Methods and Results A total of 3810 participants from the SHHS (Sleep Heart Health Study) were selected in the current study. CVD was assessed during an almost 11‐year follow‐u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Sleep has been identified as a public behavioral lifestyle health which emphasizing the impact of poor sleep on the prevalence of disease (18). Sleep quality, sleep habits, sleep duration and sleep architecture were found to be closely related to cardiovascular disease (19)(20)(21). Moreover, sleeping late was found to be associated with several MI risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep has been identified as a public behavioral lifestyle health which emphasizing the impact of poor sleep on the prevalence of disease (18). Sleep quality, sleep habits, sleep duration and sleep architecture were found to be closely related to cardiovascular disease (19)(20)(21). Moreover, sleeping late was found to be associated with several MI risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have shown that too long or too short sleep duration increased the risk of CVD, stroke, hypertension, diabetes, and metabolic syndrome [40][41][42]. Except for sleep duration, other aspects of sleep were proved to be related to chronic non-communicable diseases [43][44][45]. A study revealed the finding that sleep fragmentation was associated with higher blood glucose levels among African-Americans, and poor sleep efficiency and long wake after sleep onset increased risk of incident CVD [43].…”
Section: Discussionmentioning
confidence: 99%
“…Except for sleep duration, other aspects of sleep were proved to be related to chronic non-communicable diseases [43][44][45]. A study revealed the finding that sleep fragmentation was associated with higher blood glucose levels among African-Americans, and poor sleep efficiency and long wake after sleep onset increased risk of incident CVD [43]. As a result, comprehensive assessment of sleep should be conducted to explore its relationship with health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Furthermore, an 11-year longitudinal study from the Sleep Heart Health Study cohort (n = 3810) showed a strong inverse association between sleep efficiency, determined via at-home overnight polysomnography, and major adverse CV events. 8 However, the physiological mechanisms by which poor sleep efficiency increases CV disease risk are not well understood.…”
Section: Introductionmentioning
confidence: 99%